A monetary history of the United States, 1867-1960 - Friedman, Milton; Schwartz, Anna J. (Princeton : Princeton University Press, 1963)
This book is about the stock of money in the United States. It traces changes in the stock of money for nearly a century, from just after the Civil War to 1960, examines the factors that accounted for the changes and analyzes the reflex influence that the stock of money exerted on the course of events.
Includes index
Bibliographical footnotes.
usc 28/08/2017
Loans
Keywords: Money; Currency question; Monetary policy; Banks and banking; United States